2017
DOI: 10.1007/s11356-017-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic olive mill wastewater treatment by Fenton’s process in batch and continuous reactors operation

Abstract: Degradation of total phenol (TPh) and organic matter, (expressed as total organic carbon TOC), of a simulated olive mill wastewater was evaluated by the Fenton oxidation process under batch and continuous mode conditions. A mixture of six phenolic acids usually found in these agro-industrial wastewaters was used for this purpose. The study focused on the optimization of key operational parameters of the Fenton process in a batch reactor, namely Fe dosage, hydrogen peroxide concentration, pH, and reaction tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…It was observed that the first CSTR eliminate 30-45 % of the dye whereas the series of effect CSTR removes 70−85% of the dye. Esteves et al (2018) investigated the potential of CSTR to degrade total organic carbon (TOC) and total phenol (TPh) present in olive mill effluents using the Fenton oxidation process (continuous and batch mode).…”
Section: Continuous Stirred Tank Bioreactor (Cstr)mentioning
confidence: 99%
“…It was observed that the first CSTR eliminate 30-45 % of the dye whereas the series of effect CSTR removes 70−85% of the dye. Esteves et al (2018) investigated the potential of CSTR to degrade total organic carbon (TOC) and total phenol (TPh) present in olive mill effluents using the Fenton oxidation process (continuous and batch mode).…”
Section: Continuous Stirred Tank Bioreactor (Cstr)mentioning
confidence: 99%
“…The difference in pH value of the treated samples is due to the different effect of the individual treatments. Acidification of the solution in plasma treatment can be explained by the partial oxidation of the phenolic compounds into low molecular weight carboxylic acids, which predominantly occurs within the first stage of the Fenton process (Esteves et al 2018). In contrast, UV radiation treatment raises the pH due to the influence of different ions on the absorption of UV light and the reaction of undesirable substances with hydroxyl radicals.…”
Section: Physico-chemical Characteristicsmentioning
confidence: 99%
“…Esteves et al [41] proved the stability of the Fenton's process in continuous conditions using a continuous stirred tank reactor (CSTR) for the degradation of a phenolic mixture (vanillic, caffeic, gallic, 3,4-dihydroxyphenylacetic and coumaric acids, and tyrosol), mimicking the phenolic content of OMW. For a residence time of 120 min, [Fe 2+ ] = 100 ppm, [H 2 O 2 ] = 2.0 g/L, and T = 30 ºC, total organic carbon (TOC) and phenolic content removals of 47.5% and 96.9%, were obtained.…”
Section: Homogeneous Fenton's Processmentioning
confidence: 99%